On power structures - Bosnjak, I.; Madarasz, R. (Algebra and Discrete Mathematics, 2003)
In general, power structure of a structure A (with
universe A) is an appropriate structure defined on the power set
P(A). There are lot of papers concerning this topic in which power
structures appear explicitly or implicitly. The aim of this paper
is to give an overview of the results that are interesting from the
universal-algebraic point of view.